To solve for n in the given equation, let's simplify the expression:
3n + 1 = 4(2n - 3)
First, distribute the 4 on the right side:
3n + 1 = 8n - 12
Next, let's isolate the n term on one side of the equation. We can do this by subtracting 3n from both sides:
3n - 3n + 1 = 8n - 3n - 12
This simplifies to:
1 = 5n - 12
Now, let's isolate the n term on one side of the equation. We can do this by adding 12 to both sides:
1 + 12 = 5n - 12 + 12
This simplifies to:
13 = 5n
Finally, let's solve for n by dividing both sides by 5:
13/5 = (5n)/5
This simplifies to:
13/5 = n
So, n is equal to 13/5.
Solve for n.
Mathml image
1 answer